CakePHP application development step-by-step introduction to rapid web development using the open-source MVC CakePHP framework - Bari, Ahsanul; Syam, Anupom; Safari eBooks (Birmingham [U.K.] : Packt Pub., 2008)
"This book offers step-by-step instructions to learn the CakePHP framework and to quickly develop and deploy web-based applications. It introduces the MVC pattern and coding styles using practical examples. It takes the developer through setting up a CakePHP development and deployment environment, and develops an example application to illustrate all of the techniques you need to write a complete, non-trivial application in PHP. It aims to assist PHP programmers to rapidly develop and deploy well-crafted and robust web-based applications with CakePHP"--Resource description page.
Description based on print version record.
Includes index.
Keywords: PHP (Computer program language); Web site development; Electronic books